The Caucasus Ethnography in the Caucasus Museum Collections (second half of XIX – early XX cc.) - T. A. Kolosovskaya; A. A. Zherdev (Гуманитарные и юридические исследования)
Introduction. The paper focuses on the issue of constructing ethnographic knowledge about the Caucasus in the late imperial period. All issues of collecting, systematizing and popularizing information about the traditional cultures of local peoples are considered from an institutional aspect using materials from the Caucasus Museum.Materials and Methods. The authors characterize the role of the museum in shaping ideas about local ethnography based on a wide range of sources. The analysis of the content of ethnographic collections and their exhibition design in the context of interaction between government, science and society was carried out. It showed by what means and in what spirit this work took place.Analysis. The paper focuses on the research practices of museum director G. I. Radde and his contemporaries in creation and development of the Ethnographic Department of the museum. The author shows that quite a few famous statesmen acted as contributors of the exhibits. The main source of replenishment of the museum collections were objects of material and spiritual culture acquired by Radde during his travels in the Caucasus or as a result of interaction with other institutions and scientists. Particular attention is paid to the development of an original approach to the exhibition of ethnographic objects. The author gives various points of view of contemporaries on this issue.Results. The authors conclude that with the support of the local administration, together with G. I. Radde’s energy and hard work, the Caucasus Museum turned into a leading scientific and educational center of local ethnography. In conditions when scientific knowledge about the peoples of the region was just elaborating, he represented a collective image of the traditional culture of the East, formed in the mass consciousness of his contemporaries. His ethnographic collections showed the diversity of local peoples who had recently become Russian subjects and thereby emphasized the power and greatness of the entire Empire. The scientific significance of the Caucasus Museum, which contributes to the rise of ethnographic knowledge about the region, is also substantiated.